Complete mitochondrial genome of a troglophile Cydnidae (Hemiptera). Issue 1 (2nd January 2019) - Costa Dias, Mariana; Oliveira, Renato Renison Moreira; Vasconcelos, Santelmo; Pires, Eder Soares; Prous, Xavier; Pietrobon, Thadeu; Oliveira, Guilherme
Abstract: The complete mitochondrial genome of a specimen of Cydnidae was shotgun sequenced and each partition was characterized. This genome, with 15, 289 bp in length, has all of the 37 genes commonly found in metazoan mitochondrial genomes: two for ribosomal RNAs (rRNAs), 22 for transfer RNAs (tRNAs), and 13 for proteins. Protein-coding and ribosomal genes have a similar arrangement as in other insects. Phylogenetic relationship of this species with other family groups within the infraorder Pentatomomorpha was inferred using the maximum likelihood method based on the mitogenome. The phylogenetic analysis groups this specimen with the other Cydnidae species within the Pentatomoidea clade.